REPRESENTASI GAMBAR ANAK DALAM PERSEPSI FENOMENA PANDEMI COVID-19 DI KABUPATEN KUDUS - Fajrie, Nur; Purbasari, Imaniar (PRASI, 2024)
The background of the idea in this study describes the character and pattern of children's drawings in representing the perception of the social phenomenon of the Covid-19 pandemic with the aim of analyzing the results of children's drawings in Kudus Regency. The research method uses a qualitative approach with a case study type. The research procedure includes (1) description stage, (2) formal analysis stage, (3) interpretation stage and (4) meaning assessment stage. Data collection uses interviews from several children selected to match the experience of the Covid-19 pandemic based on age cases, regions, and the attractiveness of the events experienced. Research participants used nine works made by children in perceiving events during the Covid-19 pandemic. The results of the study have a theme of drawing works that perceive (1) self and environment; (2) religious activities; (3) prevention and health protocols; and (4) children's psychological experiences. In general, the artworks created lead to the use of techniques in simple art elements. Moral messages are more exploited in sources of knowledge from the surrounding environment. The research findings can contribute to the handling of children who experience individual problems in learning and social interaction in the community. Keywords: children's perception, drawing, aesthetic experience, covid-19   Abstrak Latar belakang adanya ide dalam penelitian ini menggambarkan karakter dan pola gambar anak dalam merepresentasikan persepsi fenomena sosial pandemi Covid-19 dengan tujuan menganalisis hasil karya gambar anak di Kabupaten Kudus. Metode penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus yang meliputi (1) tahap deskripsi, (2) tahap analisis formal, (3) tahap interpretasi, dan (4) tahap penilaian makna. Pengumpulan data menggunakan wawancara dari beberapa anak yang dipilih untuk menyesuaikan pengalaman pandemi Covid-19 berdasarkan kasus usia, wilayah, dan kemenarikan peristiwa yang dialam. Partisipan penelitian menggunakan sembilan karya yang dibuat anak dalam mempersepsikan peristiwa saat terjadi pandemi Covid-19. Hasil penelitian memiliki tema karya gambar yang mempersepsikan (1) diri dan lingkungan; (2) aktivitas religius; (3) pencegahan dan protokol kesehatan; and (4) pengalaman psikologis anak. Secara garis besar hasil karya seni yang dibuat mengarah pada penggunaan teknik pada unsur seni secara sederhana. Pesan moral lebih tereksploitasi pada sumber pengetahuan dari lingkungan sekitar. Temuan penelitian dapat memberikan kontribusi penanganan anak-anak yang mengalami persoalan individu dalam belajar dan berinteraksi sosial di masyarakat.